THE ROLE OF INTERNET IN LEARNING - Feriyanti Elina Gultom (BAHAS, 2019)
The rapid development of internet technology and penetrated to all corners of the world has been utilized by various countries, institutions, and experts for various interests including for the education world. Until now, the internet became a necessity for the world of education. Internet is a giant library of the world, because in the internet there are billions of information resources, so we can use the information according to the needs. Internet allowed students study independently. Students can access online from various libraries, museums, databases, and get a primary source of various historical events, biographies, recordings, reports, statistical data. Internet conditioned students to study independently. Students can access online from various libraries, museums, databases, and get a primary source of various historical events, biographies, recordings, reports, statistical data. Students can act as a researcher, not just information consumers only. Information is analyzed according to their learning and conduct searches that match real life. E-Learning is one of the systems or educational concepts that utilize information technology in the teaching and learning process. Students and teachers do not need to be physically present in class, as students can learn teaching materials and work on learning and exam assignments by accessing a computer network that has been set up online. Key words: Role, Internet, Learning